Technological a priori and Communicative Action in Kurt Vonnegut’s Player Piano - Mete Han Arıtürk; Mehmet Büyüktuncay (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
This article examines the state of extreme mechanization in modern industrial societies, which leads to a strict separation of the various spheres of life and ultimately to the exclusion of the human element. The philosophers of the Frankfurt School, Herbert Marcuse and Jürgen Habermas in particular, have rigorously analyzed the inherently ideological function of technology in late capitalist societies. In Player Piano, Kurt Vonnegut’s critical depiction of the extremely technologized and automated social world in a near future America slightly predates and even heralds the above-mentioned critical theorists’ analyses of the ideological nature of technology under corporate capitalism. This study scrutinizes how the technocratic state in Vonnegut’s novel utilizes technology to pacify and disempower the masses, challenging the notion that technology is merely a value-free accumulation of know-how. The devalued human subject and dehumanized society depicted in Vonnegut's anti-utopian narrative are discussed with reference to Marcuse’s notion of 'one-dimensional society' and Habermas’s theory of 'communicative action' to provide the critical framework for the analysis of the impoverishing and colonizing effects of technological rationality on the lifeworld.